2017
DOI: 10.3344/kjp.2017.30.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of amitriptyline, pregabalin, and gabapentin are preferred for management of neuropathic pain in India: is there a need for revisiting dosing recommendations?

Abstract: BackgroundCurrent therapy for the treatment of neuropathic pain is often unsatisfactory. Considerable variation in treatment pattern still exists in spite of availability of sufficient literature from various guidelines. Recent Indian market data suggested that the utilization (sale) of drugs such as amitriptyline, pregabalin, and gabapentin was more for low-dose unit packs than that of the high-dose unit packs, raising the belief that these drugs are prescribed at a lower dose than is actually recommended in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Relatively large ATL concentrations (15–60 µM) are required for the NMDAR channel block 5 . However, this somewhat contradicts clinical observations that neuropathic pain relief by ATL treatment can be rapidly achieved with dosages that are lower than those required for treatment of depression 23 .…”
Section: Introductionmentioning
confidence: 75%
“…Relatively large ATL concentrations (15–60 µM) are required for the NMDAR channel block 5 . However, this somewhat contradicts clinical observations that neuropathic pain relief by ATL treatment can be rapidly achieved with dosages that are lower than those required for treatment of depression 23 .…”
Section: Introductionmentioning
confidence: 75%
“…Neuropathic pain is one of the most challenging medical conditions after spinal cord injury (SCI) [1,2], which is associated with anxiety, depression, and sleep disorders [3][4][5]. It interferes with daily activities and normal functioning [6,7], and has a significant negative impact on the patients' quality of life [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Doses of amitriptyline (25 mg) and gabapentin (300 mg) used in the current study were less than those recommended in the British National Formulary for treatment of neuropathic pain, that is, amitriptyline 25 to 150 mg in 2 divided doses and gabapentin 1200 to 3600 mg in 3 divided doses . Kamble et al, in a questionnaire‐based survey that included 281 doctors from 31 cities in India to evaluate prescription pattern of first‐line drugs for neuropathic pain, reported that doses of amitriptyline (10‐25 mg) and gabapentin (100‐300 mg) used were low as compared to the recommendation and were found to be effective with minimal side effects. Results of the present study also suggest that amitriptyline and gabapentin can be effective in low doses, that is, 25 mg/day and 300 mg/day, respectively, in patients with zoster‐associated pain.…”
Section: Discussionmentioning
confidence: 99%